Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0083339
|View full text |Cite
|
Sign up to set email alerts
|

Nociception and Conditioned Fear in Rats: Strains Matter

Abstract: When using rats in pain research, strain-related differences in outcomes of tests for pain and nociception are acknowledged. However, very little is known about the specific characteristics of these strain differences. In this study four phylogenetically distant inbred rat strains, i.e. Wistar Kyoto (WKY), Fawn Hooded (FH), Brown Norway (BN) and Lewis (LE), were investigated in different tests related to pain and nociception. During Pavlovian fear conditioning, the LE and WKY showed a significantly longer dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…Observations made were reported both for transparency and to identify variability factors in burrowing behaviour meriting future study. Although strain differences have been reported for other outcome measures, 8 , 42 , 63 in this study, no strain differences between Sprague-Dawley and Wistar rats were observed for suppressed burrowing. Animals with a lower body weight developed an increased burrowing deficit, whereas burrowing in sham or naive groups was unaffected.…”
Section: Discussioncontrasting
confidence: 72%
“…Observations made were reported both for transparency and to identify variability factors in burrowing behaviour meriting future study. Although strain differences have been reported for other outcome measures, 8 , 42 , 63 in this study, no strain differences between Sprague-Dawley and Wistar rats were observed for suppressed burrowing. Animals with a lower body weight developed an increased burrowing deficit, whereas burrowing in sham or naive groups was unaffected.…”
Section: Discussioncontrasting
confidence: 72%
“…Cannulas were fixed to the skull using stainless steel screws and antibiotic cement (Simplex ™ P bone cement with tobramycin, Stryker Nederland B.V., The Netherlands). Anaesthesia and analgesia protocols were as previously published (Schaap et al ., , ). Briefly, rats were anaesthetized with fentanyl (0.25 mg/kg, IP – Fentanyl Janssen ® ; Janssen‐Cilag B.V., The Netherlands) and dexmedetomidine (0.15 mg/kg, IP – Dexdomitor ® ; Pfizer Animal Health B.V., The Netherlands) in their home cage.…”
Section: Methodsmentioning
confidence: 99%
“…Compounding these limitations, there is a lack of representation of female animals in fear and anxiety research, caused in part by the perceived difficulty and cost in controlling the variability associated with female animals’ reproductive cycles ( Zucker and Beery, 2010 ; Prendergast et al, 2014 ; Becker et al, 2016 ). The estrous cycle of a female rat, which is typically divided into four primary “stages” (proestrus, estrus, metestrus, and diestrus), has been linked to physiological fluctuations in synapse density in the hippocampus, amygdala, and prefrontal cortex ( Woolley and McEwen, 1992 ; Shansky et al, 2004 ; Rasia-Filho et al, 2012 ), neurogenesis in the hippocampus ( Pawluski et al, 2009 ), and behavioral variation in elevated plus-maze ( Marcondes et al, 2001 ), open field ( Frye and Walf, 2002 ), fear conditioning ( Markus and Zecevic, 1997 ; Gupta et al, 2001 ), and fear extinction tests ( Milad et al, 2009 ). Completely controlling for such fluctuations systematically would require testing animals in all test stage–estrous phase combinations, demanding greater animal numbers and substantially increasing costs.…”
Section: Introductionmentioning
confidence: 99%